The Effect of Fault Architecture on Slip Behavior in Shale Revealed by Distributed Fiber Optic Strain Sensing. Issue 1 (6th January 2022) - Hopp, Chet; Guglielmi, Yves; Rinaldi, Antonio Pio; Soom, Florian; Wenning, Quinn; Cook, Paul; Robertson, Michelle; Kakurina, Maria; Zappone, Alba
Abstract: We use Distributed Strain Sensing (DSS) through Brillouin scattering measurements to characterize the reactivation of a fault zone in shale (Opalinus clay), caused by the excavation of a gallery at ∼400 m depth in the Mont Terri Underground Laboratory (Switzerland). DSS fibers are cemented behind casing in six boreholes cross‐cutting the fault zone. We compare the DSS data with co‐located measurements of displacement from a chain potentiometer and a three‐dimensional displacement sensor (SIMFIP). DSS proves to be able to detect in‐ and off‐fault strain variations induced by the gallery excavated 30–50 m away. The total permanent displacement of the fault is ∼200 microns at rates up to 1.5 nm/s. DSS is sensitive to longitudinal and shear strain with measurements showing that fault shear is concentrated at the top and bottom interfaces of the fault zone with little deformation within the fault zone itself. Such a localized pattern of strain relates to the architecture of the fault that is characterized by a thick "layer" including an anastomosing network of polished surfaces where clay‐rich rock splits into progressively smaller flakes conferring the entire zone very little cohesion and friction (weak zone), and favoring slipping at the edges of the "layer". Overall, DSS shows that slow slip may activate everywhere there is a weak fault within a shale series. Thus, our work demonstrates the importance of shear strain on faults caused by remote loading, highlighting the utility of DSS systems to detect and quantify these effects at large reservoir scales. Plain Language Summary: Understanding how and why faults move in anisotropic shales is important for assessing the integrity of caprocks overlying geologic CO2 sequestration sites or increasing efficiency of hydraulic fracturing operations in shale gas reservoirs. Here we show that fiber optic cables can be used to accurately measure fault slip when cemented inside boreholes that intersect such a structure. This allows detecting and monitoring of a larger volume of rock than ever before. Our measurements show that a kilometers‐long fault in a clay rock, when disturbed by the excavation of a tunnel ∼30 m away, displayed localized slip mostly along its upper and lower interfaces, in contrast to a more distributed slip as would be expected with the fault core‐damage zone architecture typical of faults in competent rock. In addition, the excavation produced slip on other, smaller fractures, with slip on these planes sometimes exceeding the slip on the larger fault. These observations show how important slow slip in anisotropic shales can be in accommodating remote loading (e.g., deep reservoir pressurization or hydraulic fracturing). DSS offers new insight into whether slow slipping faults can trigger significant caprock leakage and induce earthquakes during deep injection operations. Key Points: Slow slip in a fault zone in a clay caprock concentrates on two interfaces that sharply bound the fault zone material and the intact rock Distributed strain sensing (DSS) shows equal measurand performance to potentiometers, better spatial resolution, and sensitivity to shear Activated and unactivated fractures share similar orientations; activated fractures contain scaly clay